Approach for Protection of Iris Template using Cancelable Biometrics - Chaudhary, Sheetal; Nath, Rajender; Kant, Chander; Kant, Surya (International Journal of Sensors Wireless Communications and Control, 2019)
Background & Objective: The most important issue concerning the security of biometric authentication systems is protection of biometric templates. This is because once the biometric template being attacked, it cannot be canceled and reissued. Thus, the intruder could avail the facilities that are meant only for the genuine user just bypassing the enrollment phase. Methods: To protect the biometric templates from attacks, it is advantageous to modify them before storing in the databases through some cancelable and non-invertible transformations. Hence, an approach based on cancelable biometrics is proposed in this paper for providing security and privacy to biometric templates. It uses left iris and right iris as input biometric traits. Different experiments are carried out to authenticate the proposed approach. Results & Conclusion: It satisfies all template protection requirements and expected to show good recognition performance without degrading it.
Keywords: iris recognition